Quashing demand or changing clients? Evidence of criminalization of sex work in the United Kingdom. (21st September 2021) - Della Giusta, Marina; Di Tommaso, Maria Laura; Jewell, Sarah; Bettio, Francesca
Abstract: The use of regulation of sex work is undergoing sweeping changes across Europe and client criminalization is becoming very widespread, with conflicting claims about the intended and actual consequences of this policy. We discuss changes in demand for paid sex accompanying the criminalization of prostitution in the United Kingdom, which moved from a relatively permissive regime under the Wolfenden Report of 1960, to a much harder line of aiming to crack down on prostitution with the Prostitution (Public Places) Scotland Act 2007 and the Policing and Crime Act of 2009 in England and Wales. We make use of two waves of the British National Survey of Sexual Attitudes and Lifestyles (NATSAL2, conducted in 2000–2001 and NATSAL3, conducted in 2010–2012) to document the changes in both the amount of demand for paid sex and in the type of clients that have taken place across the two waves, and their possible implications for policies that frame prostitution as a form of crime.